1932
DOI: 10.1136/adc.7.41.249
|View full text |Cite
|
Sign up to set email alerts
|

The Position of the Large Intestine in Infants and its Relation to Constipation

Abstract: The work presented in this paper was undertaken, first, to ascertain the differences in shape and position of the large intestine in infants, especially of the iliac and sigmoid colons; and, secondly, to see if there is any real relation between any of these types and constipation in infants.Anatomy.-A short account of the anatomical characters of the descending colon, iliac and sigmoid portions of the large intestine in adults will help much to the appreciation of the differences we came across in these porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1937
1937
1951
1951

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…From consideration of this clinical grouping it is quite clear that anatomical abnormalities of the colon do not inevitably cause constipation, and the success of a simple regime in cases showing elongation and/or dilatation seems to me to provide weighty evidence against the possibility of such anatomical conditions ever directly causing constipation. This view is supported by the observations of Khalik,Erfan, and Askar (1932),who found that anatomical variations in the length and calibre of the colon were common in infants who did not suffer from constipation. In the presence of faecal stasis it is conceivable that the pbssession of a long colon may increase and tend to perpetuate the condition by so altering the alignment of the large bowel-that the massive ontward nmovenment of its contenits preliminary to defaecation is impeded.…”
Section: Physiology Of Defaecationsupporting
confidence: 57%
“…From consideration of this clinical grouping it is quite clear that anatomical abnormalities of the colon do not inevitably cause constipation, and the success of a simple regime in cases showing elongation and/or dilatation seems to me to provide weighty evidence against the possibility of such anatomical conditions ever directly causing constipation. This view is supported by the observations of Khalik,Erfan, and Askar (1932),who found that anatomical variations in the length and calibre of the colon were common in infants who did not suffer from constipation. In the presence of faecal stasis it is conceivable that the pbssession of a long colon may increase and tend to perpetuate the condition by so altering the alignment of the large bowel-that the massive ontward nmovenment of its contenits preliminary to defaecation is impeded.…”
Section: Physiology Of Defaecationsupporting
confidence: 57%